Response of Phytogenic Additives on Enteric Methane Emissions and Animal Performance of Nellore Bulls Raised in Grassland - Teobaldo, Ronyatta Weich [UNESP]; Cardoso, Abmael da Silva; Brito, Thais Ribeiro [UNESP]; Leite, Rhaony Gonçalves [UNESP]; Romanzini, Eliéder Prates [UNESP]; Granja-Salcedo, Yury Tatiana; Reis, Ricardo Andrade [UNESP] (MDPI, 2022)
The objective of this study was to evaluate the intake and digestibility of nutrients, emission of enteric CH4, and productive performance of Nellore bulls grazing Urochloa brizantha cv. Marandu palisade grass pastures during the rainy season, receiving an energy supplement or mineral supplement, with or without the inclusion of phytogenic additives. Forty-eight Nellore bulls were treated with: (1) energy supplement without the inclusion of phytogenic additives; (2) energy supplement with the inclusion of phytogenic additives; (3) mineral supplement without the inclusion of phytogenic additives; and (4) mineral supplement with the inclusion of phytogenic additives. Consumption of total dry matter (DM), crude protein (CP), apNDF, and energy; digestibility of DM, CP, and energy; average daily gain; stocking rate; and gain per area were higher in animals consuming energy supplements than those consuming mineral supplements. Digestibility of DM, NDF, and energy levels were lower in animals that consumed phytogenic additives. Compared with mineral supplements, the supply of energy supplements provides higher nutrient intake, increases enteric CH4 emission, and improves nutrient digestibility, providing a greater productive performance. The inclusion of phytogenic additives negatively affected nutrient intake and digestibility, did not reduce enteric CH4 emission, and influenced productive performance.
Keywords: cattle; enteric methane; essential oils; hydrolyzable tannins; supplementation